“Trojan horse” malware as a mean for obtaining evidence in Italy - Francesco Caprioli (Revista Brasileira de Direito Processual Penal)
The Italian code of criminal procedure doesn’t regulate investigations realized with “Trojan horse” malwares located in an electronic device like a smartphone or a tablet. This study explains in which cases, and under what conditions, investigations like these can be nevertheless considered as admissible according to the Italian procedural law, and reports the contents of the main legislative proposals concerning this matter that are currently being discussed in the Italian Parliament.